Functional high-throughput screen identifies microRNAs that promote butyrate-induced death in colorectal cancer cells - Saira R. Ali; Karen J. Humphreys; Kaylene.J. Simpson; Ross A. McKinnon; Robyn Meech; Michael Z. Michael (Elsevier, 2022)
The gut fermentation product butyrate displays anti-cancer properties in the human proximal colon, including the ability to inhibit proliferation and induce apoptosis in colorectal cancer (CRC) cells. A natural histone deacetylase inhibitor (HDACi), butyrate can alter histone acetylation patterns in CRC cells, and thereby regulate global gene expression, including the non-coding transcriptome and microRNAs (miRNAs). Dysregulated miRNA expression affects CRC development and progression; however, the interplay between miRNA activity and butyrate response remains to be elucidated. A high-throughput functional screen was employed to identify miRNAs that can act as enhancers of the anti-cancer properties of butyrate. Validation studies confirmed that several miRNAs, including miR-125b, miR-181a, miR-593, and miR-1227, enhanced apoptosis, decreased proliferation, and promoted cell-cycle arrest in the presence of butyrate. Pathway analyses of predicted miRNA target genes highlighted their likely involvement in critical cancer-related growth pathways, including WNT and PI3K signaling. Several cancer-associated miRNA targets, including TRIM29, COX2, PIK3R3, CCND1, MET, EEF2K, DVL3, and NUP62 were synergistically regulated by the combination of cognate miRNAs and butyrate. Overall, this study has exposed the potential of miRNAs to act as enhancers of the anti-cancer effects of HDAC inhibition and identifies specific miRNAs that might be exploited for therapeutic benefit.